INOVASI PERANGKAT PEMBELAJARAN SISTEM KELISTRIKAN OTOMOTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Yahya, Wachid (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
This research aimed to develope of device learning in automotive electrical systems using direct instruction to improve students? learning result. Learning device with 4D models were tested to one-group pretest-posttest design. The test examined 23 students? of XI Teknik Kendaraan Ringan (TKR) SMK Negeri 3 Surabaya in the second semester with materials ?automotive electrical systems?. The data of this research were collected using three techniques namely observation, test and questionnaire. The data were then analyzed using an analysis of device validity. The results of this study show the learning equiptment is valid to be implemented, including: (a) valid syllabus with very good category, (b) valid lesson plan with very good category, (c) valid students? work sheet (LKS) with good category, (d) valid LP, (e) valid learning modul with good category,(f) valid trainer and video with good category. In addition, the learning equipment is effective to be implemented, with: (a) very good category (100%) in lesson plan implementation, (b) very good students? learning activities, (c) very good students? respond, (d) the improvement of passing score in learning result. Based on the finding above, it can be concluded that the automotive electrical system learning using direct instruction to improve students learning result is appropriate to use. Key words : The Inovation of Device Learning, Automotive Electrical Systems, Direct Instruction, Learning Result.